Antimicrobial Activity of Useful Parts of Woodfordia fruticosa (Linn.) Kurz. of Nepal - Bhattarai, Shandesh (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT In continuation of our screening of Nepalese medicinal plants, six extracts (two each of methanol, chloroform and hexane) prepared from leaf and flower samples of Woodfordia fruticosa were screened for antimicrobial activity against 14 microorganisms by disk diffusion method. The tested plant parts are used to treat ailments thought to be caused by bacterial infection, including boils, diarrhea, dysentery, fever, cough, menstrual disorders, and others. Among six extracts examined, 66% extracts showed antimicrobial property against Bacillus subtilis; 50% extracts against Staphylococcus aureus, Salmonella Typhi, Salmonella paratyphi, Citrobacter frendii each; 33% extracts against Pseudomonas aeruginosa, Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae, Shigella dysenteriae each, and 16% extracts against Enterobacter spp., Acenitobacter spp., each. Extracts were more likely to inhibit Gram-positive bacteria with respect to Gram-negative bacteria. The importance of Woodfordia fruticosa in Nepal can perhaps be understood by the broad spectrum of its antibacterial activity. We hope that this study will encourage the researchers in Nepal to explore alternative, affordable and easily available medicines of plant origin.